Biochar Enriched with Buffalo Slurry Improved Soil Nitrogen and Carbon Dynamics, Nutrient Uptake and Growth Attributes of Wheat by Reducing Leaching Losses of Nutrients - Hafiz Muhammad Rashad Javeed; Mazhar Ali; Imtiaz Ahmed; Xiukang Wang; Ibrahim Al-Ashkar; Rafi Qamar; Abdullah Ibrahim; Muhammad Habib-Ur-Rahman; Allah Ditta; Ayman EL Sabagh (Land, 2021)
The present investigation was conducted to understand the role of enriched biochar on soil nitrogen and carbon dynamics, leaching losses of nutrients, and growth attributes of wheat. Buffalo slurry (BS) was used to enrich the biochar for 24 h and 2% biochar (SB) or enriched biochar (SEB) was used. Enrichment of biochar with BS as SEB improved the C and N contents of biochar by 33–310% and 41–286% respectively. The application of biochar (SB) and enriched biochar (SEB) reduced the net nitrification by 81% and 94%, ammonification by 48% and 74%, and carbon dioxide by 50% and 92% respectively as compared to control. The leaching losses minerals i.e., C (by 30%), N (by 125%), P (by 50%), K (by 82%), Na (by 9%), Ca (by 24%), and Mg (by 12%) was decreased in SEB treatments compared to control. The soil enzyme activities, microbial biomass (MBC and MBN), wheat agronomy, soil bulk density and soil pore density, mineral uptake from the soil, and mineral contents in the plant body were improved in the SEB as compared to SB and control treatments. Our results revealed that the biochar enrichment process could improve the C and N storage in the soil reservoir and lower the environmental risks to soil and water.